Constraining surface carbon fluxes using in situ measurements of carbonyl sulfide and carbon dioxide. Issue 2 (27th February 2014) - Berkelhammer, M.; Asaf, D.; Still, C.; Montzka, S.; Noone, D.; Gupta, M.; Provencal, R.; Chen, H.; Yakir, D.
Abstract Understanding the processes that control the terrestrial exchange of carbon is critical for assessing atmospheric CO2 budgets. Carbonyl sulfide (COS) is taken up by vegetation during photosynthesis following a pathway that mirrors CO2 but has a small or nonexistent emission component, providing a possible tracer for gross primary production. Field measurements of COS and CO2 mixing ratios were made in forest, senescent grassland, and riparian ecosystems using a laser absorption spectrometer installed in a mobile trailer. Measurements of leaf fluxes with a branch‐bag gas‐exchange system were made across species from 10 genera of trees, and soil fluxes were measured with a flow‐through chamber. These data show (1) the existence of a narrow normalized daytime uptake ratio of COS to CO2 across vascular plant species of 1.7, providing critical information for the application of COS to estimate photosynthetic CO2 fluxes and (2) a temperature‐dependent normalized uptake ratio of COS to CO2 from soils. Significant nighttime uptake of COS was observed in broad‐leafed species and revealed active stomatal opening prior to sunrise. Continuous high‐resolution joint measurements of COS and CO2 concentrations in the boundary layer are used here alongside the flux measurements to partition the influence that leaf and soil fluxes and entrainment of air from above have on the surface carbon budget. The results provide a number of critical constraints on the processes that control surface COS exchange, which can be used to diagnose the robustness of global models that are beginning to use COS to constrain terrestrial carbon exchange.